pull down to refresh

Only figured it out for symmetric triplets...
Assume (a, b, c) = (x - d, x, x + d) for some x and d. The sum and product of the triplet are:
  • Sum:
(x - d) + x + (x + d) = 3x.
  • Product:
(x - d) \cdot x \cdot (x + d) = x \cdot (x^2 - d^2).
We set the sum equal to the product:
3x = x(x^2 - d^2).
Assuming x \neq 0, divide both sides by x:
3 = x^2 - d^2.
This leads to the equation:
x^2 = d^2 + 3.
Thus, x = \sqrt{d^2 + 3}. For x to be a natural number, d^2 + 3 must be a perfect square.
  • For d = 1:
    x^2 = 1^2 + 3 = 4 \quad \Rightarrow \quad x = 2.
    The triplet is (x - d, x, x + d) = (1, 2, 3).
No other values of d yield a perfect square for x^2, because d^2 + 3 is not a perfect square for d > 1.